miRNAs in the Expression Regulation of Dopamine-Related Genes and Proteins in Endometrial Cancer - Michał Czerwiński (MDPI AG, 2021)
Disruption of the dopaminergic system leads to many diseases, including cancer. Dopamine and its receptors are involved in the regulation of proliferation, cell death, invasion, and migration. Better understanding of the mechanisms involved in these processes could reveal new molecular markers and therapeutic targets. The aim of this study was to determine the expression profile of dopamine-related genes and proteins in endometrial cancer and to assess whether miRNAs are involved in its regulation. Sixty women were recruited for the study: 30 with endometrial cancer and 30 without cancer. The expression profiles of dopamine-related genes were determined in endometrial tissue samples using microarrays and qRT-PCR. Then, protein concentration was determined with the ELISA test. In the last step, miRNA detection was performed using microarrays. The matching of miRNAs to the studied genes was carried out using the TargetScan tool. The analysis showed DRD2 and DRD3 overexpression, with a reduction in DRD5 expression, which could be due to miR-15a-5p, miR-141-3p, miR-4640-5p, and miR-221-5p activity. High levels of OPRK1 and CXCL12, related to the activity of miR-124-3p.1 and miR-135b-5p, have also been reported. Low COMT expression was probably not associated with miRNA regulation in endometrial cancer.